Collaborating Online in Christian Course Design: A Case Study - Saba, Christine (Christian education journal, 2025)
This article presents a qualitative case study of how educators working for a Bible college in the northeastern United States collaborated remotely to design online courses. The study explored planning and process, building relationships, and faith at work and provides feedback and sentiments from 11 of 177 project participants who collaborated in online teamwork to complete the project. Data were collected through interviews, written responses, and a collection of examples of online communication. The findings showed that meaningful collaboration involved more than individuals producing quality work. Collaboration was enhanced through relationship building, open communication, and effective working processes. The findings of this study may also have practical implications for other Christian colleges and seminaries seeking to move course content online and more broadly for effective workings of vocational church ministry in online settings.